Effects of Hinokitiol and Dicalcium Phosphate on the Osteoconduction and Antibacterial Activity of Gelatin-Hyaluronic Acid Crosslinked Hydrogel Membrane In Vitro - Kai-Chi Chang; Wen-Cheng Chen; Ssu-Meng Haung; Shih-Ming Liu; Chih-Lung Lin (Pharmaceuticals, 2021)
Many hydrogel-based crosslinking membranes have been designed and tailored to meet the needs of different applications. The aim of this research is to design a bifunctional hydrogel membrane with antibacterial and osteoconducting properties to guide different tissues. The membrane uses gelatin and hyaluronic acid as the main structure, 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride as the crosslinker, hinokitiol as the antibacterial agent, and dicalcium phosphate anhydrous (DCPA) micron particles for osteoconduction. Results show that the hydrogel membrane with added DCPA and impregnated hinokitiol has a fixation index higher than 88%. When only a small amount of DCPA is added, the tensile strength does not decrease significantly. The tensile strength decreases considerably when a large amount of modified DCPA is added. The stress–strain curve shows that the presence of a large amount of hinokitiol in hydrogel membranes results in considerably improved deformation and toughness properties. Each group impregnated with hinokitiol exhibits obvious antibacterial capabilities. Furthermore, the addition of DCPA and impregnation with hinokitiol does not exert cytotoxicity on cells in vitro, indicating that the designed amount of DCPA and hinokitiol in this study is appropriate. After a 14-day cell culture, the hydrogel membrane still maintains a good shape because the cells adhere and proliferate well, thus delaying degradation. In addition, the hydrogel containing a small amount of DCPA has the best cell mineralization effect. The developed hydrogel has a certain degree of flexibility, degradability, and bifunctionality and is superficial. It can be used in guided tissue regeneration in clinical surgery.